Effect of measurement errors on predicted cosmological constraints from shear peak statistics with large synoptic survey telescope - Bard, D.; Kratochvil, J.; Chang, C.; May, M.; Kahn, S.; Alsayyad, Y.; Ahmad, Ziad; Bankert, J.; Connolly, A.; Gibson, R.; Gilmore, K.; Grace, E.; et al. (Institute of Physics Publishing, 2013)
We study the effect of galaxy shape measurement errors on predicted cosmological constraints from the statistics of shear peak counts with the Large Synoptic Survey Telescope (LSST). We use the LSST Image Simulator in combination with cosmological N-body simulations to model realistic shear maps for different cosmological models. We include both galaxy shape noise and, for the first time, measurement errors on galaxy shapes. We find that the measurement errors considered have relatively little impact on the constraining power of shear peak counts for LSST.